Mechanical properties and Mullins effect in rubber reinforced by montmorillonite - Białkowska, Anita; Przybyłek, Małgorzata; Sola-Wdowska, Marta; Masař, Milan; Bakar, Mohamed (Bulletin of the Polish Academy of Sciences Technical Sciences, 2023)
The present work investigated the properties of rubber vulcanizates containing different nanoparticles (Cloisite 20A and Cloisite Na+) and prepared using different sonication amplitudes. The results showed that a maximum improvement in tensile strength of more than 60% over the reference sample was obtained by the nanocomposites containing 2 wt.% Cloisite 20A and 1 wt.% Cloisite Na+ and mixed with a maximum amplitude of 270 µm. The modulus at 300% elongation increased by approximately 18% and 25% with the addition of 2 wt.% Cloisite 20A and 3 wt.% Cloisite Na+, respectively. The shape retention coefficient of rubber samples was not significantly affected by the mixing amplitude, while the values of the softness measured at the highest amplitude (270 µm) were higher compared to those of mixtures homogenized with lower amplitudes. The loading-unloading and loading-reloading processes showed similar trends for all tested nanocomposites. However, they increased with increasing levels of sample stretching but were not significantly affected by filler content at a given elongation. More energy was dissipated during the loading-unloading process than during the loading-reloading. SEM micrographs of rubber samples before and after cycling loading showed rough, stratified, and elongated morphologies. XRD results showed that elastomeric chains were intercalated in the MMT nanosheets, confirming the improvement of mechanical properties. The difference between the hydrophilic pristine nanoclay (Cloisite Na+) and organomodified MMT (Cloisite 20A) was also highlighted, while the peaks of the stretched rubber samples were smaller, regardless of the rubber composition, due most probably to the decrease of interlayer spacing.